EFFECTS OF ADDED GROUND CORN GRAIN ON THE NUTRITIONAL VALUE AND PROTEIN DEGRADABILITY OF AN ENSILED MIXTURE OF COMMON VETCH AND OATS - Stojanović, Bojan (Journal of Agricultural Sciences (Belgrade), 2025)
Abstract: The aim of the study was to determine the effects of the addition of ground corn grain (CG) on the ensiling properties, nutritional value, and protein degradability of a forage mixture of common vetch and oats. Wilted and chopped vetch-oat forage was ensiled without treatment (VO) or after treatment with 50 or 100 g/kg (wet weight) of ground corn grain (VO+5% CG or VO+10% CG). The addition of CG significantly increased the dry matter content of silages (p
Keywords: maize, legume-cereal silage, protein fractions, protein degradability, fermentation parameters.